Complex Use of B-Luron Supplement in Knee Osteoarthrosis: a Prospective Randomized Study - Vladimir Yu. Ulyanov; Natalya A. Romakina; Tatyana Yu. Kalyuta; Angelina A. Yurkovets; Aleksandr S. Fedonnikov (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
INTRODUCTION. Knee osteoarthrosis (KO) among the adult population often leads to permanent disability, a sharp decrease in the quality of life, and chronic use of analgesics. At the same time, according to the clinical guidelines of the Russian Rheumatology Association for osteoarthrosis treatment, hyaluronic acid medications are included in the list recommended for KO, and they are particularly effective at stages I-II of the disease. AIM. Evaluation of the efficiency of the dietary supplement B-Luron for KO patients within 12 weeks therapy. MATERIAL AND METHODS. A total of 70 patients with stage I-II deforming osteoarthrosis (DOA) were followed up, consecutively included in the study from December 14, 2021 to January 31, 2022, for an average of 90 days (3 months). RESULTS AND DISCUSSION. The efficiency of B-Luron for I-II DOA stages was shown: a statistically significant decrease in the level of pain in knee joints, an improvement in the function of the joint were found compared to the initial state. The analysis of objective data showed a positive trend in ultrasound parameters and MRI features of joint inflammation and a decrease in the need for analgesics within 12 weeks. CONCLUSION. In a prospective randomized clinical trial with 70 knee DOA patients as a part of the combination therapy (12 weeks use) with non-steroidal anti-inflammatory drugs, B-Luron showed its efficiency for stages I-II of the disease; there was a positive trend in ultrasound parameters and MRI signs of inflammation in the joints as well as a decrease in the need for non-steroidal anti-inflammatory drug use.